Penerapan Model Pembelajaran Penemuan Terbimbing Untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa SMA - Tri Handayani; Samsul Arifin; Arumella Surgandini (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2019)
The ability to understand mathematical concepts is a goal that must be achieved first in learning mathematics. Therefore, students are expected to have good mathematical concept understanding skills. However, in reality the ability to understand students' mathematical concepts is still low. One mode of learning that can improve students' understanding of mathematical concepts is the guided discovery learning model. This study aims to determine whether the increased ability to understand mathematical concepts of students who use the guided discovery learning model is higher than students who use conventional learning. This type of research is a quasi-experimental study using Nonequivalent Pretest-Posttest Control Group Design. The population in this study were all students of class XI MIA Citra Kasih with a sample of class XI MIA 1 and XI MIA 2 with the sample collection technique was cluster random sampling. The test instrument in this study is a test description of the ability to understand mathematical concepts in the form of problem descriptions and non-test instruments in the form of observation sheets. Based on the hypothesis test conducted from normalized change data using the Mann Whitney U test, it was found that the increased ability to understand mathematical concepts of students who use guided discovery learning models is higher than students who use conventional learning.